The Role of Architecture in the Nutrition House as a Stunting Prevention Strategy Case Study: Gampong Lamlagang Nutrition House, Banda Aceh - Aghnia Zahrah; Dyah Erti Idawati; Ghaida Humaira (Talenta Publisher, 2025)
Stunting is a chronic problem of child growth and development due to lack of or poor nutrition for a certain period of time (Nur, Setyowati, & Rosemary, 2020). Children have the basic rights of citizens to fulfill their welfare. Therefore, this phenomenon must be considered because it affects the development of generations who will become the nation's successors (Nur, Setyowati, & Rosemary, 2020). Not only the role of the mother in the household, a joint effort to achieve stunting prevention is through the Village Nutrition House program. To create a Village Nutrition House for users, especially children, it is not only necessary to provide a building. The role of architecture is necessary and can influence child psychology. If the child's psychology is good, then the child gets adequate nutrition and nutrition into the body. The author uses qualitative research methods with data obtained through observational studies, interviews and literature studies. The data is processed to become criteria and material for consideration in the construction of ideas to obtain a design strategy for the Village Nutrition House, especially one that is child-friendly. The research location is at the Gampong Lamlagang Nutrition House which is a Pilot Project model for the implementation of the Nutrition Rumah in Banda Aceh City. With this design strategy it is hoped that it can add stimulation to children and children get a pleasant eating experience so that nutrition in children can be fulfilled.